Penerapan Prinsif Itikad Baik Dalam Kontrak Baku - Rinaldy Anugrah Akbar; Muhammad Akbar; Bella Anggraini; Rizky Ramadhan; Ummi Restu Reska R (Consensus : Jurnal Ilmu Hukum, 2024)
The basis of belief in civil law is the rule contained in an agreement, whether it is between an individual and an individual or between individuals with a legal body; a standard contract removes the basis of freedom of contracting. If the standard contract does not provide a balance of interests for each party, a reaction will emerge. As a result, the foundation of faith in the formulation and implementation of the agreement must be placed in a "fine" place. Section 3 of article 1338 of the Code of Civil Procedure states that "the consent shall be executed in good faith". Good-hearted people really trust people they think are honest. They don't hide things that could potentially cause problems later on. Each contract must be subjected to credibility testing during the pre-manufacturing, manufacture (sign-up), and post-production phases. (implementation).